(untitled) (Research, Society and Development, 2020)
The present study presents federalism as a reflection of Hannah Arendt’s thinking. The theme is problematized based on the assumption about action as one of the activities of the active life and the public space as a place for the exercise of social and political relations between the citizens of a community. From this, one can assume its purpose of cohesion for the members of this community as a guarantee of the participation of the political individual with equity in the discourse, in addition to respect for the plurality of acts of coexistence in this public decision-making space. In order to understand the concept of the term under discussion, Hannah Arendt’s studies on the term “federalism” were used as a theoretical foundation. For this reason, it is the result of republicanism as an essential theme of the author’s thought. The research is bibliographic and uses the theoretical understanding and reconstruction of Hannah Arendt’s texts: The human condition (1958), On the Revolution (1962), The promise of politics (2005) and What is politics (1993). The main result achieved relates to the understanding that the meaning of the term confers a condition of belonging and responsibility for the decision-making acts of a community, since federalism constitutes the act to establish an order and validity of common prerogatives between politics and law.